PENGUKURAN NILAI CALIFORNIA BEARING RATIO (CBR) LAPIS PERKERASAN ASPAL DENGAN ALAT DYNAMIC CONE PENETROMETER (DCP) - Budhianty, Happy; Sylviana, Rika; Damayanti, Dewi; Al Ansari, Syahrul; Santoso, Angga (Universitas Islam 45 Bekasi, 2013)
Generally, DCP is only used to measure the CBR value of soil. In this research, it is tried to introduce the possibility of appliance DCP to measure the CBR value of penetration macadam pavement. Examination was executed at the critical asphalt condition (in the day time, since high burden and temperature) and used 30o cone. DCP was placed directly at the above of pavement surface. The data was analyzed to become the CBR value by using MS - Excel Macro program. The result of this research, appliance the standard DCP with cone 30Â° applicable to measure CBR value of penetration macadam pavement. Keywords : CBR, DCP